Safety of Nurse- and Self-Administered Paediatric Outpatient Parenteral Antimicrobial Therapy - Shanthy Sriskandarajah; Brett Ritchie; Janet K. Sluggett; Jodie G. Hobbs and Karen J. Reynolds (MDPI AG, 2020)
This study aimed to compare and contrast the safety and efficacy of nurse- and self-administered paediatric outpatient parenteral antimicrobial therapy (OPAT) models of care and to identify clinical factors associated with documented adverse events (AEs). A total of 100 OPAT episodes among children aged between 1 month and 18 years who were discharged from hospital and who received continuous 24 h intravenous antimicrobial therapy at home via an elastomeric infusion device were included. All documented AEs from the case notes were reviewed by a paediatrician and classified as either major or minor. Multivariable logistic regression was used to determine associations between clinical factors and any AE. A total of 86 patients received 100 treatment OPAT episodes (49 self-administered, 51 nurse administered). The most commonly prescribed antimicrobial via continuous infusion was ceftazidime (25 episodes). Overall, an AE was recorded for 27 (27%) OPAT episodes. Major AEs was recorded for 15 episodes and minor AEs were reported in 14 episodes. The odds of an AE was increased in episodes with self-administration (adjusted odds ratio (aOR) 6.25, 95% confidence interval (CI) 1.44-27.15) and where the duration of vascular access was >14 days (aOR 1.08, 95%CI 1.01-1.15). Our findings suggest minor AEs may be more frequently reported when intravenous antimicrobials are self-administered via 24 h continuous infusions.